Strategi Forward Contract dan Open Position Dalam Menghadapi Risiko Eksposur Valuta Asing Pada Perusahaan Ekspor-Impor - Elin, Elin; Yuliarti, Almira Dwi; Mubarok, Anwar Husni; Manda, Gusganda Suria (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to examine risk management strategies related to exchange rate exposure faced by export-import companies, with a particular focus on the implementation of forward contracts and open positions. A qualitative literature review approach was employed, utilizing secondary sources such as academic journals, textbooks, and previous research reports. The findings indicate that forward contracts offer exchange rate certainty for future transactions, making them more suitable for firms prioritizing financial stability. However, their effectiveness depends on precise timing and accurate market analysis. Conversely, open positions allow the possibility of gain from favorable currency movements, but they carry higher risks if market predictions are inaccurate. These results highlight the need to align hedging strategies with a company’s risk profile, financial condition, and the global economic climate. The study recommends that firms conduct periodic evaluations of currency exposure and strengthen their market analysis capabilities as part of an integrated risk management system. Furthermore, future empirical research is needed to assess the practical effectiveness of hedging strategies across specific industry sectors.